Genomic virulence markers are associated with severe outcomes in patients with Pseudomonas aeruginosa bloodstream infection - John Karlsson Valik; Christian G. Giske; Badrul Hasan; Mónica Gozalo-Margüello; Luis Martínez-Martínez; Manica Mueller Premru; Žiga Martinčič; Bojana Beović; Sofia Maraki; Maria Zacharioudaki; Diamantis Kofteridis; Kate McCarthy; et al. (Communications Medicine)
Abstract Background Pseudomonas aeruginosa (PA) bloodstream infection (BSI) is a common healthcare-associated complication linked to antimicrobial resistance and high mortality. Ongoing clinical trials are exploring novel anti-virulence agents, yet studies on how bacterial virulence affects PA infection outcomes is conflicting and data from real-world clinical populations is limited. Methods We studied a multicentre cohort of 773 adult patients with PA BSI consecutively collected during 7-years from sites in Europe and Australia. Comprehensive clinical data and whole-genome sequencing of all bacterial strains were obtained. Results Based on the virulence genotype, we identify several virulence clusters, each showing varying proportions of multidrug-resistant phenotypes. Genes tied to biofilm synthesis and epidemic clones ST175 and ST235 are associated with mortality, while the type III secretion system is associated with septic shock. Adding genomic biomarkers to machine learning models based on clinical data indicates improved prediction of severe outcomes in PA BSI patients. Conclusions These findings suggest that virulence markers provide prognostic information with potential applications in guiding adjuvant sepsis treatments.